A Content Analysis of the Cultural Products in High-School English Language Learning Materials in Indonesia (Sebuah Analisis Konten terhadap Produk Budaya yang terdapat di dalam Materi Pembelajaran Bahasa Inggris SMA di Indonesia) - Sri Imelwaty; Suharni Suharni; Edwar Kemal; Meisya Sukmarani; Ching Yi Tien (Universitas PGRI Sumatera Barat, 2023)
This study aims to describe the representation of cultural products in English language learning materials as depicted in narrative texts for Indonesian high school students. To this end, the design of this study employed qualitative content analysis to know how cultural products are represented in narrative texts for Indonesian high school students. Initially, the narrative texts were collected from the English learning materials which were compiled and used in the teaching and learning process by the English teachers. The data of this study was gathered through document review and then coded within the analysis process. The findings of this study revealed that cultural products as depicted in those narrative texts represent the category of places, followed by artifacts and institutions. However, the category of art form has not been identified yet. These findings indicate that the cultural products have not been widely represented in the learning materials. In addition, the teacher-selected narrative texts still only showed Indonesian local cultures while their students needed to know other target cultures from around the world. This study suggests that teachers should include more cultural learning in their learning materials to build student’s knowledge and awareness of culture.